(untitled) (Journal of Gandaki Medical College-Nepal, 2017)
Community diagnosis is defined as the pattern of disease in a community described in terms of the important factors which influence the pattern -King Maurice ed (1982). It is based on collection and interpretation of the relevant data such as age, sex, population distribution by social groups, vital statistics and incidence and prevalence of important diseases of the area. As per the curriculum of Tribhuvan University, B.Sc Nursing 1st year, we were provided an opportunity to fulfill the practicum of community health nursing in the city of seven lakes of Rithepani-2, Lekhnath, Kaski from July 17th to Aug 11th 2016. Total population of Rithepani ward no 2 was 4529, male population was 2100 and female population was 2429 respectively. Each of the five students was assigned with ten different families for community diagnosis in order to promote the health of the individual, family and community. The main objective of community diagnosis was to find out the health related aspects and to provide preventive, promotive curative and rehabilitative services to the individual and community as a whole. All the findings were presented among the key members of the community. On survey total population of 50 houses was found 239, among them 126 were male population and 113 were female population. Sanitation of the community was found appropriate. Moreover immunization services among under five children was adequate. Likewise, antenatal, intranatal and postnatal care was found appropriate and effective in all the houses. This signifies that people are utilizing the all health services in an appropriate manner. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 63-65